Aggregate densification in the thickening of flocculated suspensions in an un-networked bed. (27th January 2015) - Spehar, Rudolf; Kiviti-Manor, Anat; Fawell, Phillip; Usher, Shane P.; Rudman, Murray; Scales, Peter J.
Abstract: Experimental data from batch settling tests on polymer flocculated suspensions was used to determine the material properties that quantify dewatering behaviour and relate settling rate to solids concentration. These material properties were subsequently used to predict the performance of a pilot-scale gravity thickener, including the expected solids concentration profile in the thickener. Analysis of data from a novel laboratory fluidisation rig, used to simulate the hindered settling zone of a thickener, and the pilot-scale thickener, indicates that relative to simple batch settling tests, the dewatering behaviour and related material properties of flocculated aggregates change over time, even at concentrations less than the gel point of the suspension and in the absence of mechanical shear. The change is primarily attributed to the phenomenon of aggregate densification as a result of aggregate-aggregate buffeting and manifests as enhanced settling and increased thickener throughput. A fluidisation case study using calcite with no added mechanical shear (only that due to fluidisation) found that the aggregates densified to 86% of their original diameter over a period of order 4000 s. This was enhanced with the addition of mechanical shear with a further decrease in aggregate size to 76% of their original diameter. Almost identical results were observed for the pilot thickener. Laboratory data typically underestimates thickener performance, even at the pilot scale, and the agreement between laboratory and pilot results represents a novel outcome for the characterisation of material dewatering properties. The observations herein are an important step towards full-scale thickener modelling incorporating aggregate densification effects due to shear. Highlights: Aggregate densification is shown to be critical to understanding thickening. Aggregate densification is correlated at both a laboratory and pilot scale. A novel technique is demonstrated to characterise densification changes in shear. The concentration and shear dependencies of densification are demonstrated.